2010
DOI: 10.1103/physrevb.82.094302
|View full text |Cite
|
Sign up to set email alerts
|

Two types of excited electron dynamics in zinc oxide

Abstract: We present first-principle evaluations of the electron-phonon coupling strength parameter and associated characteristics of relaxation for the excited electrons in the conduction band of zinc oxide. The evaluations are based on the pseudopotential plane-wave approach to the electronic band structure, the density-functional perturbation theory for the calculations of phonons and electron-phonon interactions, and on the "Fermi golden rule" for evaluations of the electron relaxation time and the energy-loss time.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
51
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 36 publications
9
51
0
Order By: Relevance
“…Although the account of these processes is ultimately necessary to describe the electromechanical response of ferroelectrics to an applied electric field, they are not included in common statistical models of polarization response, such as the Kolmogorov-Avrami-Ishibashi (KAI) 7-10 , the nucleation limited switching (NLS) [11][12][13] and the inhomogeneous field mechanism (IFM) [14][15][16] models, dealing with statistically independent parallel 180 • switching processes only. Furthermore, experimental results revealed that both 180 • and non-180 • switching events are required in order to describe the electrical and mechanical response of polycrystalline ceramics to an applied electric field pulse during polarization reversal [17][18][19] .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although the account of these processes is ultimately necessary to describe the electromechanical response of ferroelectrics to an applied electric field, they are not included in common statistical models of polarization response, such as the Kolmogorov-Avrami-Ishibashi (KAI) 7-10 , the nucleation limited switching (NLS) [11][12][13] and the inhomogeneous field mechanism (IFM) [14][15][16] models, dealing with statistically independent parallel 180 • switching processes only. Furthermore, experimental results revealed that both 180 • and non-180 • switching events are required in order to describe the electrical and mechanical response of polycrystalline ceramics to an applied electric field pulse during polarization reversal [17][18][19] .…”
mentioning
confidence: 99%
“…Another origin of uncertainty of interpretation of experimental results within the MSM model consists in the simplifying assumption of the uniform electric field all over the system. This assumption does not allow explanation of dispersive polarization and strain responses at later switching stages 23 , which may result from the distribution of local switching times due to the spatially inhomogeneous distribution of the applied field 14,15,25 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The details of the calculations are similar to those discussed in the Refs. [26,27]. In order to confirm the acceptability of such simplifications we show in Fig.…”
Section: Resultsmentioning
confidence: 62%
“…So we can neglect the light attenuation in the bulk and apply the spectral distribution of light in vacuum admitted in the EinsteinPlanck theory. A second support is provided by the firstprinciple calculations of the band structure of anatase, rutile, and zinc oxide and evaluations of the rate of electronphonon relaxation in these species [26,27]. They demonstrate that the electron-phonon relaxation of the excited electrons to the bottom of the CB occurs within the time interval of some tens of femto-seconds, whereas, the electrons near the bottom of the CB reside a time a few orders longer.…”
mentioning
confidence: 96%